Time-dependent non-linear buckling of 3D CFST arch structures with hybrid random interval uncertainties. (15th March 2023) - Wu, Binhua; Gao, Kang; Feng, Jinpeng; Wu, Gang; Featherston, Carol A.; Gao, Wei; Zhao, Weigang
Highlights: Time-dependent nonlinear buckling behaviour of 3D concrete-filled steel tubular (CFST) arch structures considering both random and interval uncertainties were investigated. Critical nonlinear limit and bifurcation buckling loads were formulated using Chebyshev surrogate model strategy combined with finite element method. The present method can accurately predict the critical buckling loads and load–displacement paths at any time of the loading age. The present approach is capable of analysing nonlinear buckling of complex 3D structures with hybrid random interval uncertainties. Abstract: Limit point and bifurcation buckling loads are critical concerns in structural stability design. With the inevitable viscoelastic effects of creep and shrinkage in concrete, such critical buckling points may vary due to the time-dependent change of equilibrium configuration. Furthermore, the intrinsic uncertainty and natural randomness in the geometry and material characteristics would affect the structural stability performance significantly. The present study provides a new robust method, called the generalized Chebyshev surrogate model-based sampling approach, in assessing the time-dependent nonlinear buckling behaviour of 3D concrete-filled steel tubular (CFST) arch structures when both random and interval uncertainties are involved. In the proposed approach, the relationships between the uncertain parameters and the critical nonlinear limit and bifurcation buckling loads are formulated using Chebyshev surrogate model strategy combined with finite element method. The extreme bounds of the statistical features, including means, standard deviations, of the critical nonlinear buckling loads are furnished by using Monte Carlo method and Quasi Monte Carlo simulation method. Finally, the applicability and the validity of the proposed approach are illustrated with a series of numerical investigations.